Soldiers once and still : Ernest Hemingway, James Salter & Tim O'Brien - Vernon, Alex, 1967- (University of Iowa Press, 2004)
As the world enters a new century, as it embarks on new wars and sees new developments in the waging of war, reconsiderations of the last century's legacy of warfare are necessary to our understanding of the current world order. In Soldiers Once and Still, Alex Vernon looks back through the twentieth century in order to confront issues of self and community in veterans' literature, exploring how war and the military have shaped the identities of Ernest Hemingway, James Salter, and Tim O'Brien, three of the twentieth century's most respected authors. Vernon specifically explores the various way.